2022
DOI: 10.3389/fpsyg.2021.769584
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Complex Trauma and Attachment Patterns in Intimate Partner Violence

Abstract: ObjectiveEven if the relationship between adverse childhood experiences and intimate partner violence (IPV) has already been established, there are no sufficient studies examining the relationships between these factors and attachment representations, specifically attachment disorganization. Thus, this study aimed to explore, in a sample of women who experienced IPV (a) the presence of interpersonal adversities during childhood, and (b) attachment representations, with a particular focus on disorganization.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 46 publications
1
11
0
Order By: Relevance
“…Of the 26 papers addressing the relationship between childhood maltreatment experiences and risk for difficulties with partner relationships, 24 supported a relationship between exposure to childhood maltreatment and increased risk for intimate partner violence victimization 14 -16,61 -64,67,78,80,81,83,89,91,93,96 -106 and early sexual initiation, 94 including 6 supporting these increased risks during the perinatal period, 67,94,97,98,105,106 8 in adolescents and transitional age people, 15,16,67,78,80,81,83,94 and 16 in adults of reproductive age. 14,61 -64,89,91,93,96,99 -105…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of the 26 papers addressing the relationship between childhood maltreatment experiences and risk for difficulties with partner relationships, 24 supported a relationship between exposure to childhood maltreatment and increased risk for intimate partner violence victimization 14 -16,61 -64,67,78,80,81,83,89,91,93,96 -106 and early sexual initiation, 94 including 6 supporting these increased risks during the perinatal period, 67,94,97,98,105,106 8 in adolescents and transitional age people, 15,16,67,78,80,81,83,94 and 16 in adults of reproductive age. 14,61 -64,89,91,93,96,99 -105…”
Section: Resultsmentioning
confidence: 99%
“…With respect to the impact of maternal exposure to interpersonal violence (including childhood maltreatment experiences +/− intimate partner violence), out of 29 relevant articles, 25 reported on early mother-child relational outcomes. 107 -109 Of these studies, 19 reported on mother-child attachment or relationship quality, 14,105,110 -125 10 on maternal sensitivity or responsiveness, 107,108,110,112,113,121,122,126 -128 one on maternal reflective function, 128 one on maternal structuring, 129 four on maternal intrusiveness, 110,119,126,128 one on parenting competence, 130 two on harsh parenting, 110,119 two on negative infant emotionality, 107,108 two on child internalizing symptoms, 111,115 three on child externalizing symptoms, 111,115,121 and one reporting on total child psychiatric symptoms. 131 Overall, less optimal internal working models and severity of maternal mood or PTSD symptoms and alexithymia were associated with more negative parenting behaviors, lower reflective function, and negative offspring outcomes 105,110,112,113,…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations